Introduction: a taxonomy of genebank value - Smale, Melinda; Koo, Bonwoo (International Food Policy Research Institute, 2003)
How much is a collection of plant genetic resources worth? Why do economists hesitate to place a value on it? Plant genetic resources generate economic value with multiple dimensions that are difficult to conceptualize. Only a few of these dimensions can be measured and related to a market price that is a basis for valuation. Scientific nuances complicate measurement. For example, the definition of the genetic unit to be valued depends on the crop and the farming-system context, and whether the units can be added together depends on how closely they resemble one another.